Delayed radical prostatectomy after a period of active surveillance is not associated with the use of secondary treatments compared with immediate prostatectomy. Issue 3 (2nd December 2021) - Arcot, Rohith; Cher, Michael L.; Qi, Ji; Linsell, Susan M.; Dunn, Rodney L.; George, Arvin K.; Montie, James E.; Ginsburg, Kevin B.; ,
Abstract: Background: We evaluated the use of secondary treatments in men with grade group (GG) 1 PC following a period of active surveillance (AS) compared with men undergoing immediate radical prostatectomy (RP) to evaluate what is potentially lost in terms of cancer control, if a patient trials AS and transitions to treatment. Methods: We reviewed the Michigan Urological Surgery Improvement Collaborative (MUSIC) registry for men with GG1 PC undergoing RP from April 2012 to July 2018. Men were classified into groups based on time from diagnosis to RP: immediate (surgery within 1 year of diagnosis) and delayed RP (surgery >1 year after initiation of AS). Time to secondary treatment was estimated using Kaplan–Meier curves and compared using the log‐rank test. A multivariable Cox proportional hazards model was fit to assess the association between timing of RP and use of secondary treatments. A chi‐squared test was used to assess the association between delayed RP and adverse pathology. Results: We identified 1878 men that underwent an RP during the study period, of which 1489 (79%) underwent immediate RP and 389 (21%) underwent delayed RP. The incidence of adverse pathology was higher in men with delayed versus immediate RP (49% vs. 36%, p  < 0.0001, respectively). However, we noted only a small absolute difference in the estimated 24‐month secondary treatment‐free probability between men with delayed versus immediate RP (93% and 96%, respectively). On multivariable analysis, delayed RP was associated with increased use of secondary treatments (hazard ratio = 1.94, 95% confidence interval = 1.23–3.06, p  = 0.004). Conclusions: The use of secondary treatment after RP in men with GG1 PC undergoing immediate or delayed prostatectomy was rare. These data suggest that the burden of treatment is near equivalent in patients who progress to treatment on AS compared with those who underwent immediate RP.